Gender Differences in the Relationship Between Diabetes-Specific Quality of Life and Depressive Symptoms in Middle-Aged and Older Korean Immigrants - Choi, Sarah E. (2013)
This study examined age and gender differences in the relationship between diabetes specific quality of life (DQOL) and depressive symptoms among Korean immigrants with type 2 diabetes (DM). In this cross-sectional study, 160 Korean immigrants with DM aged between 40 and 80 years were assessed for depressive symptoms, DQOL, and related demographic, clinical, and psychosocial factors. The relationship between DQOL and depressive symptoms was stronger for men than women. Whereas there were no main effects of age or gender in predicting depressive symptoms, there was a significant three-way interaction between gender, age (middle-aged or older), and DQOL on depressive symptoms, with older men demonstrating the strongest positive association between DQOL and depression. Age and gender differences should be considered for DQOL and depressive symptoms in diabetic Korean immigrants. Efforts to address DQOL may be likely to have the greatest impact on decreasing depressive symptoms when targeting older male Korean immigrants.